Amphiphiles Self-Assembly: Basic Concepts and Future Perspectives of Supramolecular Approaches - Domenico Lombardo; Mikhail A. Kiselev; Salvatore Magazù; Pietro Calandra (Advances in Condensed Matter Physics)
Amphiphiles are synthetic or natural molecules with the ability to self-assemble into a wide variety of structures including micelles, vesicles, nanotubes, nanofibers, and lamellae. Self-assembly processes of amphiphiles have been widely used to mimic biological systems, such as assembly of lipids and proteins, while their integrated actions allow the performance of highly specific cellular functions which has paved a way for bottom-up bionanotechnology. While amphiphiles self-assembly has attracted considerable attention for decades due to their extensive applications in material science, drug and gene delivery, recent developments in nanoscience stimulated the combination of the simple approaches of amphiphile assembly with the advanced concept of supramolecular self-assembly for the development of more complex, hierarchical nanostructures. Introduction of stimulus responsive supramolecular amphiphile assembly-disassembly processes provides particularly novel approaches for impacting bionanotechnology applications. Leading examples of these novel self-assembly processes can be found, in fact, in biosystems where assemblies of different amphiphilic macrocomponents and their integrated actions allow the performance of highly specific biological functions. In this perspective, we summarize in this tutorial review the basic concept and recent research on self-assembly of traditional amphiphilic molecules (such as surfactants, amphiphile-like polymers, or lipids) and more recent concepts of supramolecular amphiphiles assembly which have become increasingly important in emerging nanotechnology.